Advancing smarter and more secure industrial applications using AI, IOT, and blockchain technology - Chelliah, Pethuru Raj; Saini, Kavita 1976- (IGI Global, 2021)
"This book articulates and accentuates various AI algorithms, fresh innovations in the IoT and blockchain spaces explaining how suggested AI algorithms come in handy in producing predictive and prescriptive insights out of big data